Le corps plastique dans l’œuvre dramatique de Beckett : image, matière, mouvement, geste - CHRISTOFI, Christakis (Studia Universitatis Babeș-Bolyai Dramatica, 2015)
The Plastic Body in Beckett’s Drama: Image, Material, Movement, Gesture. The body, its language and representation, what it conditions and expresses are at the center of Beckett’s stage poetry. Stage constitutes a privileged space for its exhibition, whilst everything is associated with plastic significance. This plastic body is introduced into a set of procedures, and Beckett puts it on stage. Its plasticity is interconnected with images, materials, movements and gestures, creating its own complexity to the eye of the spectator. It is conditioned by and interacts with its stage surroundings, incorporating several tensions.